Progress and challenges in maternal health care in China - Tang, Li; Pan, X.; Lee, Andy; Binns, Colin (Nova Science Publishers, Inc, 2013)
Objective: Improving women's health is an essential public health task, especially for developing countries. It is acknowledged that the enhancement of women's health attributes directly to the progress of maternal health care. The aim of this paper is to review the progress in maternal health care in China during last two decades (l990- 2010). Method: Electronic databases were systematically searched to identify studies reporting on maternal health care in China. The search strategy included the following keywords: maternal health services, maternal behaviours, prenatal care and postnatal care. Results: There has been substantial improvement in maternal health in China during the two decades up to 2010. The maternal mortality ratio (MMR) dropped from 120 per hundred thousand live births in 1990 to 30 per hundred thousand in 2010, one of the fastest reported declines anywhere in the World. The decline in the rate of MMR was faster in rural areas than that in the city, and during this period the gap in MMR between urban and rural areas has narrowed, but there are still substantial regional differences. Wide variations still exist between the eastern, central and western regions, with the highest MMR seen in the west and the lowest in the more economically affluent east. Obstetric haemorrhage is the most common cause of maternal death in China, followed by pregnancy associated hypertension, heart disease during pregnancy, embolism, and puerperal sepsis. Most of these leading causes of maternal deaths are preventable or curable by adequate prenatal care.In the early 1990s only 20% of pregnant women received their initial prenatal visit within twelve weeks of conception, and the figure increased to 65% in 2008. The proportion of women who received prenatal care was 94% in 2010, an increase of 34% since 1993. Supervised delivery in hospital plays a key role in decreasing maternal mortality and the rate of hospital delivery rose from 38% in 1993 to 98% in 2010. Despite of these achievements in maternal health care, China also faces challenges. Firstly, the frequency of postnatal visits is still unsatisfactory with only 56% women receiving postnatal care based on a national survey in 2008. Several traditional and unscientific postpartum practices remain popular in many parts of China. Secondly, there has been a dramatic increase in the rate of caesarean sections since the 1990s and a survey carried out by the WHO in 2007-2008 reported an overall caesarean section rate of 46.2% in China. Conclusion: China has made great progress in maternal health care during last twenty years. But compared with most developed countries, there are still areas that need improvement. More attention needs to be paid to postnatal care and the caesarean section rate is higher than in many other countries.